MTRA: Multi-Tier randomized remote attestation in IoT networks. Issue 81 (March 2019) - Tan, Hailun; Tsudik, Gene; Jha, Sanjay
Abstract: Large numbers of Internet of Things (IoT) devices are increasingly deployed in many aspects of modern life. Given their limited resources and computational power, verifying program integrity in such devices is a challenging issue. In this paper, we design MTRA, a Multiple-Tier Remote Attestation protocol, by exploiting differences in resources and computational power among various types of networked IoT devices. More powerful devices equipped with a Trusted Platform Module (TPM) are verified through trusted hardware while others are verified through software-based attestation. In addition, a randomized memory region for attestation is used in MTRA to increase the entropy of the attestation responses. MTRA is a flexible means of program integrity verification for heterogeneous IoT devices.